Living in a fluid world: An autoethnographic account of navigating contradicting onto-epistemological worldviews - Nuri, Pashew (Journal of International Students, 2025)
This article employs an interpretive autoethnographic approach to explore how the author navigates the paradigmatic contradictions between poststructuralism as a theoretical framework and his personal religious beliefs. It narrates and analyzes how the researcher arrives at specific understandings of reality, knowledge, and the self. The author then examines how these understandings were challenged by poststructuralism and whether they have been reconciled. The article contributes to ongoing discussions on colonial theories and the critical importance of Asia as a method and southern theory in higher education and social theory.